Experimental investigation of natural and synthetic hybrid composite for marine application. (2020) - Dinesh, S.; Elanchezhian, C.; Vijayaramnath, B.; Sathiyanarayanan, K.; SyedAfiridi, S.
Abstract: In this investigation hybrid composite material was prepared and composed of Kevlar (K29), Eggshell and Coir fiber which are reinforced composite, fabricated by hand layup method. Various combinations of sample were prepared and test was carried out to find the Mechanical Behavior and water absorption tests as per ASTM standard. Micro structure was analyzed by SEM. Here Observed that increased tensile strength of Kevlar with coir and egg reinforced sample produced better mechanical properties and very less weight which can be used for marine application.